Penerapan Strategi Coping Untuk Mengatasi Krisis Kepercayaan Diri Dampak Pandemi Covid-19 - Ririanti Rachmayanie Jamain; Nina Permata Sari; M. Arli Rusandi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2022)
The outbreak of the Covid-19 pandemic does not only affect physical health aspects but also hurts mental health. One of them is self-confidence, which is found in students of class VIII at SMPN 25 Banjarmasin as many as 30, 92% of the 152 students identified as experiencing a crisis of self-confidence. The method used is collaborative-consultative, involving guidance and counseling teachers at SMP Negeri 25 Banjarmasin. The service subjects were 5 students of class VIII SMP Negeri 25 Banjarmasin. The activity is carried out in four stages of the meeting, namely the stage of explaining the concept and planning of coping strategies, the stage of formulating behavioral activities that must be stopped/controlled, the stage of implementing the formulation of the planned behavior activities. The results obtained were that coping strategies were very successful in helping to overcome the crisis of self-confidence during the Covid-19 pandemic. To support the consistency of positive self-confidence behavior that is formed, the counselee members are given directions to encourage each other and develop the confidence that has been obtained to continue to be consistent in a positive way and develop other aspects of positive behavior.